PERDAGANGAN LINTAS NEGARA KOMODITAS PERKEBUNAN VIA PLBN ARUK: STUDI EKSPORTASI KARET DAN KELAPA SAWIT DARI KABUPATEN SAMBAS, EVALUASI KEBIJAKAN BEA CUKAI ARUK, DAN PROYEKSI PERTUMBUHAN SEKTOR PERKEBUNAN MELALUI AGRIBISNS BILATERAL - Sari, Rafika; Hutagaluh, Oscar; Yuniarti, Desi (Lunggi Journal, 2026)
The Aruk Cross-Border Post (PLBN Aruk) in Sambas Regency, West Kalimantan, is one of the gateways for cross-border trade between Indonesia and Malaysia. The PLBN system provides opportunities to expand export access for local commodities-including plantation products such as rubber and palm oil-directly to the Malaysian market. This study evaluates the role of PLBN Aruk in the trade of plantation commodities, local customs policies, and the growth prospects of the plantation sector through bilateral agribusiness cooperation between Indonesian and Malaysian